Sevoflurane Alters Serum Metabolites in Elders and Aging Mice and Increases Inflammation in Hippocampus - Wang T; Wu X; Zhao X; Li J; Yu J; Sheng M; Gao M; Cao Y; Wang J; Guo X; Zeng K (Dove Medical Press, 2024)
Tingting Wang,1- 3,* Xia Wu,4,* Xiaoli Zhao,2,3,* Jiaqi Li,5,* Jian Yu,4 Maozheng Sheng,4 Mingyuan Gao,4 Yutang Cao,5 Jiawen Wang,6 Xiaozhen Guo,5 Kai Zeng1 1Department of Anesthesiology, Anesthesiology Research Institute, The First Affiliated Hospital of Fujian Medical University, Fuzhou, People's Republic of China; 2Seventh People's Hospital of Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China; 3Department of Anesthesiology, Changning Maternity and Infant Health Hospital, Shanghai, People's Republic of China; 4Shanghai Key Laboratory of Regulatory Biology, Institute of Biomedical Sciences and School of Life Sciences, East China Normal University, Shanghai, People's Republic of China; 5State Key Laboratory of Drug Research, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai, People's Republic of China; 6College of Life Sciences, Wuhan University, Wuhan, People's Republic of China*These authors contributed equally to this workCorrespondence: Kai Zeng; Xiaozhen Guo, Email fymzk6822@163.com; guoxz@simm.ac.cnPurpose: Postoperative cognitive dysfunction (POCD) is a central nervous system complication that occurs after anesthesia, particularly among the elderly. However, the neurological pathogenesis of postoperative cognitive dysfunction remains unclear. The aim of this study was to evaluate the effects of sevoflurane exposure on serum metabolites and hippocampal gene expression in elderly patients and aging mice by metabolomics and transcriptomic analysis and to explore the pathogenesis of sevoflurane induced POCD.Patients and Methods: Human serum samples from five patients over 60 years old were collected before sevoflurane anesthesia and 1 hour after anesthesia. Besides, mice aged at 12 months (n=6 per group) were anesthetized with sevoflurane for 2 hours or with sham procedure. Subsequently, serum and hippocampal tissues were harvested for analysis. Further investigation into the relationship between isatin and neuroinflammation was conducted using BV2 microglial cells.Results: Sevoflurane anesthesia led to the activation of inflammatory pathways, an increased presence of hippocampal astrocytes and microglia, and elevated expression of neuroinflammatory cytokines. Comparative analysis identified 12 differential metabolites that exhibited changes in both human and mouse serum post-sevoflurane anesthesia. Notably, isatin levels were significantly decreased after anesthesia. Notably, isatin levels significantly decreased after anesthesia, a factor known to stimulate proliferation and proinflammatory gene expression in microglia-the pivotal cell type in inflammatory responses.Conclusion: Sevoflurane-induced alterations in serum metabolites in both elderly patients and aging mice, subsequently contributing to increased inflammation in the hippocampus.Keywords: sevoflurane, hippocampus, neuroinflammation, RNA-seq, metabolomics, isatin